The handbook of gangs - Decker, Scott H.; Pyrooz, David (Chichester, West Sussex : Wiley Blackwell, 2015)
"Pulling together the most salient, current issues in the field today, The Handbook of Gangs provides a significant assessment by leading scholars of key topics related to gangs, gang members, and responses to gangs. Chapters cover a wide array of the most prominent issues in the field of gangs, written by scholars who have been leaders in developing new ways of thinking about the topics Delivers cutting-edge reviews of the current state of research and practice and addresses where the field has been, where it is today and where it should go in the future Includes extensive coverage"--publisher's description.
The Logic of Defining Gangs Revisited -- Little Gang Research, Big Gang Research -- Documenting Gang Activity: Intelligence Databases -- Gang Membership in a Developmental and Life-Course Perspective -- Neighborhoods and Street Gangs -- Gangs and Social Learning Theory: What We Know, What We Need to Know, and Why It Matters -- Social Psychology of Gangs: An Intergroup Communication Perspective -- Social Network Analysis and Gangs -- Gangs, Guns, and Violence: Synergistic Effects -- Gangs and Drugs: Connections, Divergence, and Culture -- Gender, Sexuality, and Gangs: Re-envisioning Diversity -- Joining the Gang: A Process of Supply and Demand -- Leaving the Gang: A Review and Thoughts on Future Research -- Micro-Level Processes of the Gang -- Street Gangs, Terrorists, Drug Smugglers, and Organized Crime: What s the Difference? -- Police Gang Units and Effective Gang Violence Reduction -- Gangs in Correctional Institutions -- Legislative Approaches to Addressing Gangs and Gang-Related Crime -- The Gang Resistance Education and Training (G.R.E.A.T.) Program: An Evaluator s Perspective -- The OJJDP Comprehensive Gang Strategy: The Comprehensive Gang Model -- The Legacy of Malcolm W. Klein -- The Legacy of Irving A. Spergel -- The Legacy of James F. Short, Jr. -- The Legacy of Walter B. Miller -- Understanding Gangs in Contemporary Latin America -- Understanding European Gangs -- European Responses to Gangs -- Gangs in African, Asian, and Australian Settings.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed July 29, 2015).
Keywords: Gangs -- Handbooks, manuals, etc; SOCIAL SCIENCE / Criminology; Gangs; Crime; Gangs; Gangsters; Electronic books; Handbooks and manuals; Electronic books